Targeting Local Recurrence After Surgery With MRI Imaging for Prostate Cancer in the Setting of Salvage Radiation Therapy - Renard-Penna, Raphaële; Zhang-Yin, Jules; Montagne, Sarah; Aupin, Laurene; Bruguière, Eric; Labidi, Mouna; Latorzeff, Igor; Hennequin, Christophe (Frontiers in Oncology, 2022)
MRI is being increasingly used for imaging suspected recurrence in prostate cancer therapy. Functional MRI with diffusion and perfusion imaging has the potential to demonstrate local recurrence even at low PSA value. Detection of recurrence can modify the management of post-prostatectomy biochemical recurrence. MRI scan acquired before salvage radio-therapy is useful for the localization of recurrent tumors and also in the delineation of the target volume. The objective of this review is to assess the role and potential impact of MRI in targeting local recurrence after surgery for prostate cancer in the setting of salvage radiation therapy.